The Cambridge handbook of forensic psychology - Brown, Jennifer; Horvath, Miranda (Cambridge University Press, 2022)
"In the decade since the publication of the first edition of The Cambridge Handbook of Forensic Psychology, the field has expanded into areas such as social work and education, while maintaining the interest of criminal justice researchers and policy makers. This new edition provides cutting-edge and comprehensive coverage of the key theoretical perspectives, assessment methods, and interventions in forensic psychology. The chapters address substantive topics such as acquisitive crime, domestic violence, mass murder, and sexual violence, while also exploring emerging areas of research such as the expansion of cybercrime, particularly child sexual exploitation, as well as aspects of terrorism and radicalisation. Reflecting the global reach of forensic psychology and its wide range of perspectives, the international team of contributors emphasise diversity and cross-reference between adults, adolescents, and children to deliver a contemporary picture of the discipline"--